In Pursuit of Justice: The Evolution of Social Work in Criminal Supervision - Hajairin Hajairin (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2024)
Social work punishment is a form of renewal of basic criminal punishment in Indonesia. Therefore, it is important to regulate the mechanism of social punishment supervision so that the implementation of social work punishment is in accordance with the objectives of punishment in Indonesia, one of which is to create a sense of security in the community. As a form of legal novelty, currently Indonesia does not have legal regulations governing the mechanism of supervision of social work punishment. The policy of social work criminal supervision greatly affects the legal framework in realizing justice. The purpose of this research is to explain the importance of legal reform in the supervision of criminal social work and provide ideas on the ideal model for criminal social work supervision in Indonesia. The method used in this research is normative juridical, by examining the application of rules or norms in positive law with a statutory approach, historical approach, and conceptual approach. The result of this research is that legal reform is needed so that Indonesia has rules governing the implementation of social work punishment in detail so that it can create justice and benefit in society. The ideal model of supervision of social work punishment in ius constituendum criminal law reform, namely by formulating a direct supervision model and using a global positioning system (GPS) by Community Supervisors and coordinating with the Prosecutor and the agency where the convict works.